ANALISIS EFISIENSI EKONOMI PENGGUNAAN FAKTOR-FAKTOR PRODUKSI PADA USAHATANI KEDELAI DI KABUPATEN SUKOHARJO - Wiwit Rahayu; Erlyna Wida Riptanti (Universitas Sebelas Maret, 2010)
The research ordering to analyze the greatest affecting of production factors to the production result in soybean farm in Sukoharjo Regency and to find out whether the farmer in Sukoharjo Regency had reached the highest economic efficiency. The main method of research was descriptive and the technique was by using survey. The research was conducted in Sukoharjo Regency. The research took 30 farmers as the sample. The samples are monoculture soybean farmer which selected by purpusive sampling. The result of the doubled-linier regression analysis performed that the production factors which gave the greatest affecting to the result of soybean production is large of land. The large of land has linier comparison effect to the production result of soybean and affected to the production result of soybean, means addition of production factor of seeds exactly will be bring increase the production result of soybean. Based on the maximum profit approach can be found out that the combination of the use of production factors in soybean farm in Sukoharjo Regency not yet optimal. It means that the soybean farm needs combination of increasing and or decreasing production factors to optimize the use of production factor.